In vitro protective effects of 2,4,6-trihydroxy-3-geranyl acetophenone on junctional protein disruption and the underlying signaling pathways in lipopolysaccharide-induced endothelial hyperpermeability - Chan, Yee Han (2022)
Endothelial hyperpermeability is a prominent hallmark in the pathogenesis of diseases such as sepsis and endotoxemia. Proinflammatory stimuli such as lipopolysaccharide (LPS) could trigger the overproduction of proinflammatory mediators and activate multiple signaling pathways, thereby resulting in junctional protein disruption and endothelial hyperpermeability. As such, inhibiting the structural and functional impairment of junctional proteins is thought to be crucial in treating endothelial hyperpermeability. 2,4,6-Trihydroxy-3-geranyl acetophenone (tHGA) is a bioactive phloroglucinol compound found inthe young leaves of Melicope pteleifolia (Champ. ex Benth.) T.G.Hartley.Previous study has proven that tHGA exhibited significant in vitro barrierprotective effects against LPS induction, mainly by inhibiting endothelialhyperpermeability via the attenuation of F-actin cytoskeletal rearrangement. Inendothelium, F-actin cytoskeleton is anchored to cell-cell junctional proteinssuch as zonula occluden (ZO)-1, occludin, and vascular endothelial-cadherin(VE-cadherin), and plays collaborative roles with them in the preservation ofendothelial integrity. Therefore, effects of tHGA on these junctional proteinsshould be further investigated. Also, more in-depth investigations are required tofurther dissect the signaling pathways mediated by tHGA in suppressing LPS-induced endothelial hyperpermeability. In the present study, Human UmbilicalVein Endothelial Cells (HUVECs) were pretreated with tHGA for 6 hours,followed by LPS induction with respective durations. The cells were divided intoseven experimental groups including vehicle control, tHGA control, LPS control,dexamethasone drug control, and tHGA treatment (1.25, 5, and 20 μM) groups.Several parameters related to endothelial hyperpermeability were assessed.Firstly, transendothelial electrical resistance (TEER) assay was performed toexamine the effect of tHGA on endothelial junctional integrity during LPSinduction. Secondly, immunofluorescence staining was conducted to evaluatethe effect of tHGA on the localization of junctional proteins along the cell periphery. Thirdly, Western Blot and Reverse Transcription-quantitative Polymerase Chain Reaction (RT-qPCR) were conducted to elucidate the effect of tHGA on the expression of junctional proteins at protein and gene level, respectively. Lastly, the effect of tHGA on the activation of several proinflammatory signaling molecules such as NF-κB p65, myosin light chain (MLC), p38 MAPK, ERK MAPK, and JNK MAPK were assessed in order to explore the signaling pathways involved in the protective effects of tHGA. The findings demonstrated that tHGA was able to preserve endothelial junctional integrity significantly at 20 μM during LPS induction. Interestingly, all concentrations of tHGA significantly preserved intact ZO-1 and VE-cadherin along the cell periphery, via the abrogation of delocalization, as evidenced by the attenuation of intercellular gap formation. In terms of expression, 5 and 20 μM tHGA exerted significant inhibitory effects against the down-regulation of ZO-1 and VE-cadherin at both protein and gene level. Interestingly, only 20 μM was able to alleviate occludin down-regulation. More in-depth investigations later found that tHGA primarily targeted GEF-H1/RhoA/ROCK pathway in the manifestation of protective effects against LPS-induced junctional protein disruption, as evidenced by its abilities to inhibit the activation of downstream signaling molecules including MLC, NF-κB p65, p38 MAPK, and ERK MAPK. In conclusion, tHGA profoundly abrogated LPS-induced endothelial hyperpermeability by suppressing the delocalization and down-regulation of junctional proteins including ZO-1, occludin, and VE-cadherin, via the inactivation of MLC, NF-κB p65, p38 MAPK, and ERK MAPK, which are mainly diverged from GEF-H1/RhoA/ROCK pathway. As such, it is highly recommended that tHGA should be further developed into a potential therapeutic remedy for treating various disorders related to uncontrolled or prolonged endothelial hyperpermeability.